Children books publication in Lithuania in 1940–1955 - Mozūraitė, Vita (Knygotyra, 1992)
The State Publishing House of Lithuanian SSR and some private publishing houses published children books at the period from June 1940 untill June 1941. They published 49 children books in 277,5 thousand copies. At the time of german occupation children books were published in Moscow, where the State Publishing House had worked, and some in Lithuania. After the end of war in 1945 new publishing houses were created in Lithuania and all of them had published books for children. The main part of children books were published by the State Publishing House of Fiction Literature. During eleven years 588 children books ware published in 9345.4 thousand copies. Fiction books totaled 85,9% of that number.Censorship, shortage of translators and editors hindered publication of children books. At first their prices were very large, but from 1949 they began to go down. Often the publication was slopped by shortage of illustrators of children books or by their unsatisfactory work. A Section of Children Literature and a Commission of illustrators in the Union of writers and in State Publishing House of Fiction Literature were created on purpose of improving the publication of children books. Middle edition of the children book nad grown for 2.5 times from 1945 till 1955.